THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN MEDICAL DIAGNOSTICS - Sadulloeva Mashkhura Adizovna; Rakhmonova Mohinur Isroilovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Artificial intelligence (AI) has become one of the most transformative technologies in modern healthcare. Its integration into medical diagnostics has improved accuracy, speed, and accessibility of clinical decision-making. This paper reviews the current applications of AI in diagnostic imaging, early disease detection, clinical data analysis, and personalized medicine. Challenges and future perspectives of AI-based healthcare systems are also explored.